Evaluation of buffaloes reproductive performance in Akabiluru Subdistrict, West Sumatra - Reswati; Salam Ningsih Aritonang (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This study aimed to evaluate the reproductive performance of adult female buffaloes on smallholder farms in Akabiluru Subdistrict, Lima Puluh Kota Regency, West Sumatra. The method used was a survey through direct observation and structured interviews using questionnaires. Respondents were selected by purposive sampling, namely farmers with adult female buffaloes that have given birth at least twice, with 66 people with 71 female buffaloes.  The parameters observed included age at first mating, service per conception (S/C), age at first calving, and calving interval. Data were analyzed descriptively by calculating the average, standard deviation, and percent. The results showed that the age at first mating (33.17±7.84 months) and S/C (1.62±0.85) were within the optimal range. However, the age at first calving (46.17±10.36 months) and calving interval (23.46±7.03 months) were not optimal. Efforts are needed to improve farmers' reproductive management skills, feed quality, and technical training to improve buffalo reproductive performance and farmer welfare in Akabiluru Subdistrict.